Discursive Construction of Subject and Ideological Fantasy in Postcolonial Indonesia - Aprinus Salam (Humaniora, 2020)
This paper tries to explain the contestation at the discursive construction level of the subject. The subject in question is Indonesia in postcolonial era. The problem that will be answered was how the ideological fantasy constructed its subject. The data were chosen purposively from several novels. The paper approach is discourse-like in nature. The results of this paper show that in the contestation there is competition of colonial discourse, modernism; in which will also crossed with religion or local values. It can be concluded that there has been overlapping ideological fantasy of Indonesian postcolonial subject.